Histopathologic Evaluation of Atypical Fibroxanthoma or Pleomorphic Dermal Sarcoma Debulk Specimen from Mohs Surgery: A Requirement for Their Proper Distinction - Muhammad N. Mahmood (MDPI AG, 2024)
Pleomorphic dermal sarcomas can be clinically aggressive, with a higher tendency to cause local recurrence, metastasis, and death. Atypical fibroxanthoma and pleomorphic dermal sarcoma are histopathologically similar, and their distinction requires a systematic examination of the entire excised tumor. Since Mohs micrographic surgery is commonly utilized to treat atypical fibroxanthoma, a histopathologic evaluation of debulk specimens by permanent pathology is prudent to avoid underdiagnosing pleomorphic dermal sarcoma. This approach can improve risk assessment and treatment decisions, ultimately enhancing patient outcomes. Also, the proper distinction will facilitate the future development of accurate staging criteria and additional treatment modalities.